The therapeutic potential of ultra-short-acting β-receptor antagonists in perioperative analgesic: Evidence from preclinical and clinical studies - Fu, Linbin; Yu, Buwei; Li, Zheng; Liu, Zhiheng (Frontiers in Pharmacology, 2022)
Perioperative multimodal analgesia can reduce the side effects of a high concentration of opioids, improving the comfort of the patient. However, insufficient analgesia of this model has prompted researchers to explore new adjuvant analgesics. Recently, an increasing number of studies have found a low-grade analgesic effect in the clinical application of ultra-short-acting β-adrenergic receptor antagonists, which are conventionally used as pharmacologic agents in the cardiovascular system. The mechanism by which ultra-short-acting β-antagonists exert antinociceptive effects has not been clarified yet. In this review, we intend to address its potential reasons from the side of neurotransmitters, inflammatory cytokines, and signaling pathways, providing theoretical proof for the application of β-adrenergic receptor antagonists in analgesia.